Global Warming Impacts Micro-Phytoplankton at a Long-Term Pacific Ocean Coastal Station - Ajani, Penelope A.; Davies, Claire H.; Eriksen, Ruth S.; Richardson, Anthony J. (Frontiers in Marine Science, 2020)
Understanding impacts of global warming on phytoplankton–the foundation of marine ecosystems–is critical to predicting changes in future biodiversity, ocean productivity, and ultimately fisheries production. Using phytoplankton community abundance and environmental data that span ∼90 years (1931–2019) from a long-term Pacific Ocean coastal station off Sydney, Australia, we examined the response of the phytoplankton community to long-term ocean warming using the Community Temperature Index (CTI), an index of the preferred temperature of a community. With warming of ∼1.8°C at the site since 1931, we found a significant increase in the CTI from 1931–1932 to 2009–2019, suggesting that the relative proportion of warm-water to cold-water species has increased. The CTI also showed a clear seasonal cycle, with highest values at the end of austral summer (February/March) and lowest at the end of winter (August/September), a pattern well supported by other studies at this location. The shift in CTI was a consequence of the decline in the relative abundance of the cool-affinity (optimal temperature = 18.7°C), chain-forming diatom Asterionellopsis glacialis (40% in 1931–1932 to 13% in 2009 onward), and a substantial increase in the warm-affinity (21.5°C), also chain-forming diatom Leptocylindrus danicus (20% in 1931–1932 to 57% in 2009 onward). L. danicus reproduces rapidly, forms resting spores under nutrient depletion, and displays a wide thermal range. Species such as L. danicus may provide a glimpse of the functional traits necessary to be a “winner” under climate change.